Artificial and natural shade: Implications for green turtle (Chelonia mydas) rookery management. (15th April 2021) - Reboul, Isabella; Booth, David; Rusli, Uzair
Abstract: Global sea turtle populations are threatened by rising atmospheric temperatures which result in higher incubation temperatures. Increased incubation temperatures affect embryo survival, hatchling sex ratio and hatchling locomotor performance. This study aimed to determine the effectiveness of natural and artificial shade on reducing green turtle ( Chelonia mydas ) incubation temperature at Chagar Hutang beach, Redang Island, Malaysia. To achieve this objective, clutches were incubated using three treatments: unshaded control, artificial shade, and natural tree shade. Estimated hatchling sex ratios, hatching success and locomotor performance were compared across the shade treatments. Clutches incubated in the shaded hatchery were on average 1.3 °C cooler than the unshaded control group, but remained above 30.5 °C and were predicted to produce 100% female hatchlings. In contrast, natural shade from the fringing forest reduced incubation temperatures by 2.7 °C relative to the unshaded clutches, and were predicted to produce up to 85% male hatchlings. Hatching success was similar across treatments and little effect of treatment was observed on hatchling locomotor performance. We recommend relocating nests at high risk of inundation or predation to natural tree shade as a viable solution for ensuring at least some male hatchling production at Chagar Hutang beach. Graphical abstract: Image 1 Highlights: We compared different shading strategies for reducing green sea turtle nest incubation temperature. Nests under natural tree shade were on average 1.4 °C than a shaded hatchery, and 2.7 °C cooler than unshaded nests. Nests in the natural tree shade were the only predicted source of male hatchlings at this site. Incubating nests under tree shade did not affect hatching success or hatchling quality.